PERENCANAAN PEMBANGUNAN E-GOVERNMENT : ANALISIS VISUAL MENGGUNAKAN VOS VIEWERS - ivan prakoso (Fakultas Seni Rupa dan Desain ITB, 2022)
The purpose of this research is to see how the strategies implemented by the government in the development of E-Government. In elaborating, we use the Literature Review research method on E-Government development planning published between 2011 and 2021 downloaded from the Scopus indexed database using the keyword E-Government Development Planning. Through VOSViewer we analyze many published articles and their relation to a topic area. This paper confirms the findings of scholars and reports that the use of electronic devices and the internet by the government has implemented the existence of E Government. In this paper, 50 articles published in per-review journals from 2011-2021 are systematically reviewed. This paper concludes that a strategy is needed in building infrastructure, online portals, and human capacity to use them. This study has significant implications for promoting sustainability in the practice of public sector organizations in country contexts around the world. The limitation of this research is that the articles presented are different from the conditions in each country so that there is a need for a critical understanding of the government system. So that the next research needs to understand the main points of the topics that are in accordance with the title and focus on research by adjusting to new things that are to be sought and can be adjusted to the title that is raised.